Adaptation and validation of BullyHARM-China—a Chinese version of the Bullying, Harassment, and Aggression Receipt Measure. (June 2023) - Yang, Jingyi; Ferraz, Raul; Shi, Dexin; Harrison, Sayward E.; Ye, Zhi; Chen, Lihua; Lin, Danhua
Bullying is a growing concern in China, yet there are few validated scales designed to measure different types of bullying among Chinese children. In this present study, a bilingual team of researchers use a forward-backward translation process to adapt the Bullying, Harassment, and Aggression Receipt Measure (BullyHARM) for Chinese youth. BullyHARM has previously been shown to be a reliable scale for measuring six bullying domains (i.e., physical, verbal, social/relational, cyber, property, sexual) among children in the United States (US). After cultural and linguistic adaptation, we enrolled 397 middle school students from Beijing, China in a validation study to assess the psychometric properties of the new BullyHARM-China scale. Results of confirmatory factor analysis suggest the final 21-item scale displays strong internal consistency. Consistent with findings from the US, the first-order model of six factors (i.e., six bullying subscales) displays the best fit to the data. Our findings suggest that BullyHARM-China is a reliable tool for measuring bullying victimization among Chinese students.